From coffee industry waste materials to skin-friendly products with improved skin fat levels - Ribeiro, Helena; Marto, Joana; Raposo, Sara; Agapito, Maria; Isaac, Vera Lucia Borges [UNESP]; Chiari, Bruna G. [UNESP]; Lisboa, Pedro F.; Paiva, Alexandre; Barreiros, Susana; Simões, Pedro (Wiley, 2013)
Spent coffee grounds (SCG), which are the residue obtained from the treatment of coffee with hot water or steam, can be used for industrial applications, due to the high content in lipids. The cosmetic products might be a suitable application for these types of residues because the barrier properties of the stratum corneum (SC) are largely dependent on the intactness of the lipid lamellae that surrounds the corneocytes. The purpose of this work was to assess the feasibility of using the lipid fraction of SCG extracted with supercritical carbon dioxide in the development of new cosmetic formulations with improved skin lipids (sebum) and hydration. The use of spent coffee lipid extract in cosmetic industry seems to be a suitable approach to recycle the wastes from coffee industry. Emulsion containing 10% of the lipid fraction of SCG (SpentCofOil cream) presented promising characteristics in the improvement of sebum skin levels with a good acceptance by consumers when compared to an emulsion containing 10% w/w of green coffee oil (GreenCofOil cream) and a placebo without coffee oil (NoCofOil cream). Practical applications: In this work, the authors develop and characterize a cream containing 10% of the lipid fraction of SCG extracted with supercritical carbon dioxide with improved skin lipids (sebum) and hydration. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: Green coffee oil; Skin fat levels; Spent coffee lipid; Supercritical fluid extraction; Topical creams